COMMENTS ON THE RESULTS OF CHORIONIC VILLUS SAMPLING AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results and diagnostic effectiveness of chorionic villus sampling at Hanoi Obstetrics and Gynecology Hospital.Research methods: A descriptive retrospective study was conducted on 102 pregnant women who underwent chorionic villus sampling from January 2022 to June 2024.Results: 100% success rate of sampling, no complications. Genetic abnormalities were detected in 49.02% of cases, including Down syndrome (18.63%), Edwards syndrome (4.90%), Patau syndrome (0.98%), sex chromosome abnormalities (3.92%), combined Edwards and sex chromosome abnormalities (0.98%), and single-gene disorders (19.61%). There was a significant correlation between high-risk NIPS and abnormal chorionic villus sampling results (p < 0.05). In 13 cases of abnormal ultrasound of organs with chromosomal abnormalities 11 cases (86.96%). Post-procedure pregnancy outcomes showed 49.02% termination due to severe genetic abnormalities, while 50.98% continued uneventfully.Conclusions: Chorionic villus sampling is an early, accurate, and safe prenatal diagnostic method, particularly effective in pregnancies with high-risk NIPS or abnormal ultrasound findings.
Keywords: Chorionic villus sampling, prenatal diagnosis, chromosomal abnormalities, single-gene disorders.